North Country - Caro, Niki, 1967-; Wechsler, Nick; Seitzman, Michael, 1967-; Theron, Charlize; McDormand, Frances; Bean, Sean; Jenkins, Richard, 1947-; Bingham, Clara; Warner Bros. Pictures (1969- ); Participant Productions; Copyright Collection (Library of Congress) (United States : Warner Bros. Pictures, 2005)
Josey Aimes works at a Minnesota steel mine after splitting with her violent husband, but the job proves to be almost as harrowing as her marriage. The male miners are resentful of women taking their jobs, so the men verbally abuse and play humiliating pranks on the female miners. After being physically assaulted by a coworker, Josey tries to fight against the harassment, but none of the other women will join her case for fear that things will get worse.
Copyright Claimant: Schematic Productions, GmbH & Co. KG. Previous Registration: Preexisting material: screenplay entitled Untitled Niki Caro project, by Michael Seitzman, some footage & recordings preexisting. Basis of Claim: NM: motion picture, incl. audiovisual & other cinematographic material. Date of Creation: 2005; Date of Publication: 2005-10-21; Registration Number / Date: PA0001299210 / 2006-02-01.
Summary adapted from FirstSearch, OCLC 62460052, viewed May 1, 2008.
Inspired by the book Class action by Clara Bingham and Laura Leedy Gansler.
Digital sound on two compact discs stored in one film can (CGD 8847).
Not viewed.
Sources used: copyright data sheet; copyright database; Variety Web site, review posted Sept. 12, 2005, viewed May 1, 2008; Internet movie database, viewed May 1, 2008; FirstSearch, OCLC 62460052, viewed May 1, 2008.
Keywords: Women miners -- Legal status, laws, etc -- Drama; Sex discrimination in employment -- Law and legislation -- Drama; Sexual harassment of women -- Law and legislation -- Drama; Class actions (Civil procedure) -- Drama; Women -- Feature; Adaptation -- Feature